Navigating professionals’ conditions for co-production of victim support: A conceptual article - Würtz Jensen, Julie Mathilde (International review of victimology, 2024)
From previous research it is well known that victimization can have various short- and long-term consequences resulting in a need for support to cope with the victimization. Research also shows, however, that not all victims of crime seek or receive support. One cause of this might be the conditions and constraints that affect professionals’ matching of support services with individual victims’ needs. The purpose of the present conceptual paper is to discuss how professionals can co-produce support services with the individual victim and if needed engage suitable external organizations for the purpose of adapting support services to the individual victim’s needs, while also considering the complex field of constraints that professionals need to navigate during this process. The paper makes two main contributions. First, it conceptualizes the complex field of constraints as consisting of five sets of conditions (mandatory, local, professional, support-user, and inter-organizational conditions), which professionals must navigate during the co-production of victim support services. Second, the paper suggests a seven-step process of how professionals can navigate this complex field during co-production of victim support services’ activities with the individual victim, and potentially those of external organizations as well.